PERLINDUNGAN HUKUM BAGI NASABAH PENGGUNA INTERNET BANKING - ALINE FEBRIANY LOILEWEN; TITIN TITAWATI (GANEC SWARA, 2019)
This study aims to examine and analyze how the legal protection and supervision of the banking world for customers using internet banking facilities.  This study uses a form of normative legal research, namely research that is based on written rules and legislation and various literature related to the problems that will be discussed in this study.   Some forms of legal protection for customers using internet banking facilities are the existence of the Financial Services Authority Regulation No.38 / POJK.03 / 2016 concerning Application of Risk Management in the Use of Information Technology by Commercial Banks (POJK IT Risk Management). The existence of Article 1 number 12 of Law No. 11 of 2008 concerning Information and Electronic Transactions (UU ITE), electronic signatures are signatures consisting of electronic information that is attached, associated or related to other electronic information used as a verification and authentication tool . Another thing that can be done by customers who use internet banking facilities is to conduct customer complaints. Customer complaints are a manifestation of the protection of rights owned by customers, namely the right to be heard. This right is regulated in Article 4 letter d of Law 8 of 1999 concerning Consumer Protection of the PK Law). Whereas in the financial services sector, there is Article 32 of the Financial Services Authority Regulation No. 1 / POJK.07 / 2013 concerning Consumer Protection in the Financial Services Sector (POJK PK) which stipulates that financial service sector business operators must have and carry out customer service and settlement complaints.  The supervision policy carried out by Bank Indonesia towards banks aims to protect the interests of the community and to maintain the continuity of the bank's business as a trust and as an intermediary institution, the supervision is carried out either directly or indirectly